Hydroxy‐Safflower Yellow A inhibits the TNFR1‐Mediated Classical NF‐κB Pathway by Inducing Shedding of TNFR1. (25th January 2016) - Wang, Haifang; Liu, Jinlian; Yang, Yuejin; Cao, Qingwen; Huo, Xueping; Ma, Shuhui; Hu, Jun; Pavalko, Fredrick M.; Liu, Qinshe
Abstract : Hydroxy‐safflower yellow A (HSYA) is the major active component of safflower, a traditional Asia herbal medicine well known for its cardiovascular protective activities. The purpose of this study was to investigate the effect of HSYA on TNF‐α‐induced inflammatory responses in arterial endothelial cells (AECs) and to explore the mechanisms involved. The results showed that HSYA suppressed the up‐regulation of ICAM‐1 expression in TNF‐α‐stimulated AECs in a dose‐dependent manner. High concentration (120 μM) HSYA significantly inhibited the TNF‐α‐induced adhesion of RAW264.7 cells to AECs. HSYA blocked the TNFR1‐mediated phosphorylation and degradation of IκBα and also prevented the nuclear translocation of NF‐κB p65. Moreover, HSYA reduced the cell surface level of TNFR1 and increased the content of sTNFR1 in the culture media. TNF‐α processing inhibitor‐0 (TAPI‐0) prevented the HSYA inhibition of TNFR1‐induced IκBα degradation, implying the occurrence of TNFR1 shedding. Furthermore, HSYA induced phosphorylation of TNF‐α converting enzyme (TACE) at threonine 735, which is thought to be required for its activation. Conclusively, HSYA suppressed TNF‐α‐induced inflammatory responses in AECs, at least in part by inhibiting the TNFR1‐mediated classical NF‐κB pathway. TACE‐mediated TNFR1 shedding can be involved in this effect. Our study provides new evidence for the antiinflammatory and anti‐atherosclerotic effects of HSYA. Copyright © 2016 John Wiley & Sons, Ltd.